Идиот: роман в 4 частях (Ф. М. Достоевский) - Достоевский Федор Михайлович (1988)
Экземпляры: БС (20170719) / Инвентарный номер: РТШ47739 / Сис.шифр: Р1 / Авт.знак: Д 70 / ГРНТИ: 17 / ББК: 84(2=411.2)-4